Archeologia, dziedzictwo archeologiczne i ich społeczne znaczenie w oczach współczesnych Polaków - Kajda, Kornelia; Pawleta, Michał; Marciniak, Arkadiusz (Folia Praehistorica Posnaniensia, 2018)
The article explores the issues connected to the social role of archaeology and its meaning among the public. In the paper we analyze the European survey conducted by Harris Interactive in 9 European countries (Poland, Greece, Italy, France, Sweden, UK, Holland, Germany, Spain) with a special account on its results in Poland. The results of the survey present that archaeology is a scientific discipline of special interest among Poles and that they appreciate and need a contact and cooperation with archaeologists which would enable society to understand more the importance of our own past.